Implementasi Nilai Persatuan dalam Membentuk Toleransi pada Keberagaman Anggota Ekstrakurikuler Pencak Silat di SMA Negeri 1 Simo, Kabupaten Boyolali - Aprilia Kanthi Prihatini; Anis Suryaningsih; Raharjo Raharjo (Lisyabab : Jurnal Studi Islam dan Sosial, 2026)
Abstract This research is motivated by the phenomenon of conflict between pencak silat schools in Boyolali Regency, which demonstrates that diversity has the potential to lead to conflict if not managed properly. However, a different situation is seen in the pencak silat extracurricular activities at SMA Negeri 1 Simo, where members from various schools are able to establish harmonious relationships. This study aims to analyze the implementation of the value of unity in fostering tolerance and identify supporting and inhibiting factors. The study used a qualitative, descriptive approach. The research subjects included mentors, coaches, and members of the pencak silat extracurricular activities selected using a purposive sampling technique. Data collection techniques included observation, in-depth interviews, and documentation. Data validity was tested using source and technique triangulation, while data analysis was conducted through data reduction, data presentation, and drawing conclusions. The results show that the implementation of the value of unity is carried out through the planning, implementation, and evaluation stages. During the implementation stage, the value of unity is realized through social interactions that place members on equal footing, cooperation in achieving common goals, and the formation of a collective identity as a school team. This process fosters an attitude of tolerance characterized by acceptance, respect, and appreciation of differences. Supporting factors include shared goals, coaching that emphasizes the values of brotherhood and sportsmanship, support from coaches and the school, and a high level of social interaction. Meanwhile, inhibiting factors include individual ego, prejudice from the external environment, and the dynamics of member turnover. Theoretically, these findings align with contact theory, which asserts that interactions under equal conditions, cooperation, shared goals, and institutional support can reduce prejudice and strengthen social relationships, while also demonstrating the formation of social integration among members. Keywords: Unity Values, Tolerance, Diversity, Pencak Silat, Extracurricular Activities.